2021
DOI: 10.51985/jbumdc054
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Association of Inflammatory Biomarkers with Severity and Mortality in COVID-19

Abstract: Objectives: To determine prognostic values and association of inflammatory markers with severity and mortality in COVID- 19 in a hospital based study. Study design and setting: This retrospective study was conducted from 1st June 2020 to 30th Sept 2020 in Department of Pathology, Qazi Hussain Ahmed Medical Complex, Nowshera and Medical Teaching Institute, Hayatabad Medical complex Peshawar. Methodology: Out of 215, 71 cases were selected that had all relevant information’s on chart available in Blood bank and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…We observed that the mean age of patients with SD in the first wave was 54 +12 years, and in the 4th wave, 56+16 years was not significantly different in both phases for hospitalized patients(p-0.571). As per our previous experience, we had reported that 35 (49.3%) of the patients had age >55 years and 25 (35.2%) among the ICU patients hospitalized due to COVID-19 11 . However, a study from India comparing the 1 wave with the 2 wave reported the younger age group was affected more in the second wave.…”
Section: Discussionsupporting
confidence: 57%
“…We observed that the mean age of patients with SD in the first wave was 54 +12 years, and in the 4th wave, 56+16 years was not significantly different in both phases for hospitalized patients(p-0.571). As per our previous experience, we had reported that 35 (49.3%) of the patients had age >55 years and 25 (35.2%) among the ICU patients hospitalized due to COVID-19 11 . However, a study from India comparing the 1 wave with the 2 wave reported the younger age group was affected more in the second wave.…”
Section: Discussionsupporting
confidence: 57%